Channel Patterns And Margins Of Agroindustry Coffee Powder Cap Coffee In Dusundi Seluma District - Putra, Prayudha Aerlangga; Fariadi , Herri; Andriani, Evi (Utami Publisher, 2025)
One of the household agroindustry at Seluma regency is Coffee powder with brand Kopi Dusun at Desa Talang Benuang, Air Periukan subdistrict, Seluma regency. This business purpose is to fulfill the demand by consumers (market) and one of the household revenues for the producer of the coffee themselves. The purpose of this research is to find out the marketing channel patten and analyze the marketing margin of Kopi Dusun product at Seluma regency. Data analysis method used in this research is marketing channel and marketing margin analysis. From the research it can be found that the channel of coffee market in Seluma regency has 5 patterns, they are from agroindustry to distributors to retailer and to consumers. (2) From agroindustry to distributor to consumers. (3) From agroindustry to distributors and consumers directly come to distributors.(4) Retailers come to agroindustry and sell it to consumers. (5) Consumers directly comes to agroindustry. Marketing margin of the Kopi Dusun Product on Marketing channel I is product Kopi Dusun with weight (50gr) for RP. 3.000, weight (100gr) for Rp. 3.000 and weight (200gr) for Rp. 4.000. The margin for marketing channel II weight (50gr) for Rp. 2.000, weight (100gr) also Rp. 2.000 and for weight (200gr) for Rp. 2.000. Marketing Margin of Kopi Dusun onchannel pattern III for weigh (50gr) isRp 1.000, weight (100gr) also Rp 1.000 and for (200gr) is Rp 1.000. For marketing channel patten IV for weight (50gr) is Rp 3.000, weight (100gr) also Rp 3.000 and weight (200gr) for Rp 4.000. Marketing channel V with size (50gr) is Rp 0.000, weight (100gr) also Rp 0.000 dan for weight (200gr) for Rp 0.000.